Valorization of Seafood Processing Discards: Bioconversion and Bio-Refinery Approaches - Venugopal, V. (Frontiers in Sustainable Food Systems, 2021)
The seafood industry generates large volumes of waste. These include processing discards consisting of shell, head, bones intestine, fin, skin, voluminous amounts of wastewater discharged as effluents, and low-value under-utilized fish, which are caught as by-catch of commercial fishing operations. The discards, effluents, and by-catch are rich in nutrients including proteins, amino acids, lipids containing good proportions of polyunsaturated fatty acids (PUFA), carotenoids, and minerals. The seafood waste is, therefore, responsible for loss of nutrients and serious environmental hazards. It is important that the waste is subjected to secondary processing and valorization to address the problems. Although chemical processes are available for waste treatment, most of these processes have inherent weaknesses. Biological treatments, however, are environmentally friendly, safe, and cost-effective. Biological treatments are based on bioconversion processes, which help with the recovery of valuable ingredients from by-catch, processing discards, and effluents, without losing their inherent bioactivities. Major bioconversion processes make use of microbial fermentations or actions of exogenously added enzymes on the waste components. Recent developments in algal biotechnology offer novel processes for biotransformation of nutrients as single cell proteins, which can be used as feedstock for the recovery of valuable ingredients and also biofuel. Bioconversion options in conjunction with a bio-refinery approach have potential for eco-friendly and economical management of seafood waste that can support sustainable seafood production.